The Effect of Emotional Intelligence on Team Performance: Case study in Government Hospital - S, Lukman (Manunggal Halim Jaya, 2024)
Organizational development requires human resources. Professional organizations manage systems and organizational mechanisms of existing resources to support flexible change responses. Hospitals, as one of the service industries with a very complex business process, certainly have enormous potential for optimization and efficiency improvements. The study aims to explore the relationship between emotional intelligence and team performance during the inter-institutionalized collaboration work process. This study was conducted in hospitals in South Sulawesi and Central Sulawesi Province. The study lasted for 6 (six) months in 2017. The sampling was done using cluster method and stratified random sampling based on Hospital Type and level of Health Officers. The data analysis approach used in this study was Partial Least Square (PLS) using WarpPLS software. The results show that emotional intelligence significantly and positively affected the team performance with a path coefficient value of 0.138 and a p-value (of 0.050). Based on the data analysis results, there is a significant direct influence between Emotional intelligence and team performance.